ANALISIS PENGARUH SENSUAL MARKETING TERHADAP MINAT BELI PADA PRODUK CLOTHING LINE â€œBERAKâ€ DI INSTAGRAM - Pratama, Jimmy Ary; Adhilla, Fitroh (Universitas Ahmad Dahlan, 2016)
This research is to find out whether there is a significant influence between sensual marketing strategies that are triggered by a model, body language, and nature how to communicate with buying interest in